Analysis of the Science Perspective of the Qur'an Surah Al-Alaq Verses 1-5) - Eva Fitri Yunengsih (Aslim: Journal of Education and Islamic Studies, 2024)
A library is an information center that stores and manages various information. The library is also a means of preserving library materials as a cultural product as well as a function of a source of scientific and technological information. The role of libraries is so important in the future of a nation. Libraries are a source of knowledge, learning resources and information sources for all levels of society. Therefore, libraries must continue to strive to help people enjoy reading so that they become an intelligent generation. One of the arguments that obliges us to seek knowledge is (QS. Al-alaq [96] verses 1-5). In QS. Al-alaq [96] verses 1-5 contain the argument for Allah SWT's command, for humans to read. The command to read in Surah Al'alaq means that by reading you will gain knowledge. Reading has a very broad meaning, namely, reading the text of the Koran or writing and reading which includes studying the nature of its contents. The command to read in Surah Al'alaq aims to ensure that Muslims in particular and humanity in general have knowledge or literacy and information literacy. By having knowledge and information literacy, humans are able to master the world. There is a saying "Read and the world is in your hands."